2016
DOI: 10.3928/23258160-20160229-05
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Intraoperative Dexamethasone Intravitreal Implant and Triamcinolone Acetonide Used During Vitrectomy and Epiretinal Membrane Peeling: A Case Control Study

Abstract: Both intraoperative DEX and IVTA, used at the completion of vitrectomy and at membrane peeling for epiretinal membrane, were effective in improving visual and anatomic outcomes, though there was a trend toward greater significance with IVTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…compared the visual and anatomic outcomes of idiopathic ERM eyes undergoing PPV with intraoperative use of either intravitreal dexamethasone implants or IVTA found no differences between the two treatments. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…compared the visual and anatomic outcomes of idiopathic ERM eyes undergoing PPV with intraoperative use of either intravitreal dexamethasone implants or IVTA found no differences between the two treatments. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Besides the study by Yonekawa et al . [ 11 ] only one other study by Guidi et al . investigated the effects of simultaneous injections of dexamethasone implants during PPVs for ERM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, triamcinolone has been found to last approximately 113 days in vitrectomized eyes [15], while intravitreal dexamethasone implant has been shown to be 6 times more effective than triamcinolone [24]. However, Yonekawa et al [26] reported a similar trend between triamcinolone and intravitreal dexamethasone implant regarding anatomical and functional outcomes in patients affected by macular pucker and treated with PPV, although this was a retrospective study without a control group. On the other hand, in a case series of 5 patients, Taney et al [20] showed that intravitreal dexamethasone implant was beneficial for persistent macular edema after PPV for ERM, although repeated injections were needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, both studies were limited by a relatively small sample size and lack of control group. Yonekawa et al reported that both dexamethasone intravitreal implant and triamcinolone acetonide are effective in improving central macular thickness and visual acuity while the intraoperative dexamethasone intravitreal implant or triamcinolone acetonide is used after vitrectomy and membrane peeling [40]. However, recently, Guidi et al reported that the intraoperative sustained-release dexamethasone implant did not result in a significant change in macular thickness and volume compared with the vitrectomy alone without dexamethasone implant at 6-month follow-up [42].…”
Section: Discussionmentioning
confidence: 99%